The application of mathematics to social studies instruction in the high school - Rebollos, Grace C. Jimeno 1952- (1978)
This paper has been presented as one more material aimed at bridging the gap between social studies and mathematics. The advantages of mathematics have been extensively discussed by various authors cited in the second and third chapters of this paper. The fourth chapter was devoted to an inventory, a listing of selected social studies concepts and mathematical competencies related to them. These were further applied to some teaching guides dealing with the manner in which mathematics can be used to open, develop, or culminate lessons in social studies. All avenues are open for creativity and the teacher is encouraged to guide his students into a joint venture at investigating social phenomena through their competencies in mathematics.